Pharmacokinetics of Ceftaroline in a Preterm Infant With Methicillin-Resistant Staphylococcus Aureus Pneumonia. (16th October 2017) - Salerno, Sara N; Bernhardt, Janice; Laughon, Matthew; Jhaveri, Ravi; Massaro, Matthew; Gonzalez, Daniel
Abstract: We report here the first pharmacokinetic–pharmacodynamic relationship for ceftaroline in a preterm infant born at <28 weeks' gestational age who was given ceftaroline (8.5 mg/kg every 8 hours) for pneumonia attributable to methicillin-resistant Staphyloccocus aureus . This dose of ceftaroline was adequate to achieve the pharmacodynamic endpoint associated with efficacy for methicillin-resistant Staphyloccocus aureus .